Nanoporous Materials and Their Applications - Pergher, Sibele; Rodríguez-Castellón, Enrique (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book is a special collection of articles dedicated to the preparation and characterization of nanoporous materials, such as zeolitic-type materials, mesoporous silica (SBA-15, MCM-41, and KIT-6), mesoporous metallic oxides, metal–organic framework structures (MOFs), and pillared clays, and their applications in adsorption, catalysis, and separation processes. This book presents a global vision of researchers from international universities, research centers, and industries working with nanoporous materials and shares the latest results on the synthesis and characterization of such materials, which have given rise to the special interest in their applications in basic and industrial processes.